Factors Affecting Employee Retention Strategies Hospitality Sector - et. al., Seema Chawla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the highly competitive environment of hospitality industry, retention of competent employees who will become core employees for organisations is essential. Effective employee retention strategies help the organisations in hospitality sector to retain their talented and competent employees and achieve improvement in performance. This study aims to identify the factors affecting employee retention strategies in Indian hospitality sector. The confirmatory factor analysis method was used to analyze the responses received from the employees working with the different rated hotels located in NCR region of India The findings of the study indicated that organisation culture and values, monetary rewards and incentives, learning and career growth, organisation initiation, organisational leadership, work life balance and exit barriers have significant influence on retaining employees in Indian hospitality organisations.